Heart rate in paediatric patients: normal ranges and abnormalities - Bellsham-Revell, Hannah (Henry Stewart Talks, 2025)
Heart rate in paediatric patients, Paediatric Early Warning System (PEWS) ranges, Normal and abnormal heart ranges, Tachycardia, Bradycardia, ECG, Rhythm disturbances in children and adults, Supraventricular Tachycardia (SVT), Atrial Tachycardia (AT) and Heart block